The Moderating Effect of Sustainability Reporting on the Influence of Tax Avoidance on Firm Value - Hendi; Pramesti, Desinta; Harsono, Budi (Yayasan Ilomata, 2024)
The purpose of this research is to obtain empirical evidence supporting the hypothesis that sustainability reports can reduce shareholders' negative reactions to tax avoidance. The selected research sample consists of non-financial companies listed on the Indonesia Stock Exchange over a period of five years (2018-2022). The research data were tested using panel regression methods. The results of the test on 1.690 observation data indicate that only 40% of the samples engage in sustainability reporting. This suggests that a considerable number of publicly listed companies in Indonesia do not engage in sustainability reporting. The results of the analysis indicate that tax avoidance does not have a significant impact on the company's value. Sustainability reporting as a moderating variable has a positive effect on the relationship between tax avoidance and the company's value. Several control variables have a significant impact on firm value, namely leverage, profitability, and plant assets. This study contributes to the analysis of the impact of tax avoidance on the value of companies in Indonesia, moderated by sustainability reporting.